1996
DOI: 10.1093/jmedent/33.6.952
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Ribosomal DNA–Polymerase Chain Reaction Species Diagnostic Assay for the Common Malaria Mosquito (Diptera: Culicidae) Sibling Species Complex

Abstract: A polymerase chain reaction method for identifying individuals in the Anopheles quadrimaculatus Say sibling species complex was validated for wild mosquitoes from Louisiana and Mississippi. This method distinguished An. quadrimaculatus species A, B, C, and D by detecting species-specific differences in the 2nd internal transcribed spacer of ribosomal DNA and was 100% specific and 95% sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…[20] will be necessary to confirm their utility. In order to ensure that the IMP primer sets would function correctly in strains other than those we analysed and for which sequence data was available, reported sequences were examined [1,12,21-23] and no polymorphisms were found that would interfere with the success of the protocol.…”
Section: Resultsmentioning
confidence: 99%
“…[20] will be necessary to confirm their utility. In order to ensure that the IMP primer sets would function correctly in strains other than those we analysed and for which sequence data was available, reported sequences were examined [1,12,21-23] and no polymorphisms were found that would interfere with the success of the protocol.…”
Section: Resultsmentioning
confidence: 99%
“…Neben dem COI-Gen existieren zahlreiche Arbeiten zu speziesspezifischen ITS-Regionen der ribosomalen DNA bei systematisch weit entfernten Organismen (BESANSKY et al, 1992;FERRIS et al, 1993;FRITZ et al, 1994;HACKETT et al, 2000;HARRIS & CRANDALL, 2000;PASKEWITZ & COLLINS, 1989;RUTLEDGE et al, 1996;MILLER et al, 1999;FABRY et al, 1999;GALLEGO & GALIAN, 2001 Arten zu diagnostizieren bzw. komplizierte Arten zu diskriminieren und entsprechend nach geeigneten Primerpaaren und Enzymen suchen zu können.…”
Section: E R G E B N I S S E U N D D I S K U S S I O Nunclassified
“…Subsequent to this review, a variety of molecular methods for identifying anopheline species have appeared in the literature, offering more accurate and efÞcient alternatives (Walton et al 1999). These alternatives include the use of the polymerase chain reaction (PCR) with species-speciÞc primers, diagnostic allozymes, randomly ampliÞed polymorphic markers (RAPDS), and probes (Cooper et al 1991, Hill and Crampton 1994, Audho et al 1995, Fritz et al 1995, Wilkerson et al 1995, Rutledge et al 1996, West et al 1997.…”
mentioning
confidence: 99%